Two Levels Data Fusion Filtering Algorithms of Multimode Compound Seeker - Zhang Guodong; Liu Zhong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The multimode compound guidance is an important guidance system which can assurance missile impact accuracy in the complicated electromagnetic environment. Aiming at the data fusion filtering problem of multimode compound seeker, this paper presents a two-stage data fusion algorithm. First of all, each sensor data is send into first-stage fusion structure for centralized fusion processing after time registration, and then the processing results are sent into second-stage fusion structure for distributed fusion processing with radar and infrared information processing results. Meanwhile, in order to solve the problems that the different observation information in distributed fusion structure has different dimensions, the observation data is extended to the same dimension. Simulation results show that the proposed algorithm can effectively improve the data fusion efficiency, and improve the efficiency of the filter convergence accuracy and convergence speed, which has a certain guiding significance to engineering practice. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2696